IPad for seniors for dummies - Muir, Nancy 1954- (--For dummies, 2010)
Your iPad is an e-book reader, music player, movie screen, online shopping center, mailbox, and more-- all in a device small enough to take anywhere. Learn how to set it up and use its features, including great options that make life a lot easier if you have vision or hearing challenges.